Implementation of Risk Management at PMI City of Surakarta - Sri Partini; Agus Setyo Utomo; Fannyza Putri Thalia (International Journal of Seocology, 2023)
PMI Surakarta City is a social humanitarian and non-profit organization. Served to assist the government and must be responsible for all operational activities of the organization. This organization must be independent and must be ready to face any and all problems that occur. In the face of various possibilities and risks, negative and positive impacts. Risk management will have many benefits for the organization. To find out whether PMI Surakarta implements risk management and how it is implemented. This research is a qualitative descriptive and quantitative study with data collection, data observation with in-depth interviews and documentation and field studies at PMI Surakarta City during the implementation of risk management in April – June 2023. There are organizational benefits by implementing risk management. Risk management encourages organizations to achieve organizational goals optimally, targets are met effectively and efficiently. In the process of risk management stages, the results of risk analysis, risk data that are likely to occur, are analyzed, evaluated, managed and treated according to risk management, so that risks that are likely to occur and have an adverse impact on the organization can be prevented or avoided. Even the risk of the possibility of having a negative impact can be used as an opportunity to become a positive impact in improving organizational performance. Negative impacts or impacts that harm the organization if they can be avoided and managed properly by the organization, the costs that must be incurred by the organization will be more efficient. And compared to when the organization has to deal with or accept the negative impacts and losses that have occurred, the costs will be much more efficient, meaning that organizational performance will increase. PMI Surakarta City has implemented risk management. And the risk management process can further enhance organizational performance. With an analysis of existing risks, and with risk management according to risk management, various risks that have an adverse impact can be managed and can become opportunities for the organization. So that by implementing risk management properly, organizational performance can be maximized and as expected.